MANAJEMEN ARUS KAS DAN STRUKTUR MODAL SEBAGAI PENENTU KEBERHASILAN KEUANGAN PADA EDGAR ADVERTISING - Bonefasius Radit Doulet; Istiono Istiono (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to analyze the influence of cash flow management and capital structure on the financial success of Edgar Advertising during the period of August 2024 to August 2025. The study used a qualitative descriptive method with data obtained through documentation of internal financial reports (cash flow, balance sheet, income statement) and direct interviews with the company's finance department. The results of the study indicate that efficient cash flow management plays a significant role in maintaining the company's liquidity and operational smoothness. Meanwhile, a capital structure dominated by equity (77–78%) and relatively small accounts payable (11–13%) helps maintain long-term financial stability. The combination of these two factors has a positive effect on the company's financial success, as indicated by an 8% increase in net profit, a 15.6% increase in assets, and a 14.3% increase in owner's equity during the study period. Thus, it can be concluded that effective cash flow management and a healthy capital structure proportion are the main factors in maintaining the financial stability and success of Edgar Advertising.